Outbreaks of Ips typographus (L.) (Coleoptera Scolytidae) in spruce stands of Northern Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Outbreaks of the spruce bark beetle have caused considerable damage to the coniferous woods of the Orobie Prealps in Northern Italy. From 1985 to 1989 more than 40 hectares of forest were destroyed and more than 2000 trees felled. The present paper show the evolution of these outbreaks and the results of these controlling effects with trap trees and pheromone baited traps and also some short critical notes on these methods of control.
Keywords: Ips typographus; outbreaks; pheromone-baited traps; trap trees